On The Response Of A Non-Uniform Beam Transvered By Mobile Distributed Loads (Global Journal of Science Frontier Research, 2012)
The problem being investigated in this paper is that of the response of non-uniform beam under tensile stress and resting on an elastic foundation. The fourth order partial differential equation governing the problem is solved when the beam is transverse by mobile distributed loads. The elastic properties of the beam, the flexible rigidity, and the mass per unit length are expressed as functions of the spatial variable using Struble's method. It is observed that the deflection of non-uniform beam under the action of moving masses is higher than the deflection of moving force when only the force effects of the moving load are considered. From the analysis, the response amplitudes of both moving force and moving mass problems decrease with increasing foundation constant.
Keywords: Distributed Load; Non-uniform; Elastic Foundation; moving Mass